Match struck [videorecording (DVD)] - Rhodes, Tiffany; Rhodes, Tiffany; Katt, George; Koechner, David, 1962- (Indican Pictures, 2023)
An infamous writer desperate to redeem herself takes the idea of jumping into the creative process into a whole new world that blurs the lines between fiction and reality!